Pelatihan Penanganan Pasca Cabut Gigi dengan Chlorhexidine bagi Dokter Gigi di Sidoarjo: Training on Post-Tooth Extraction Care with Chlorhexidine for Dentists in Sidoarjo - Indrawati, Dwi Wahyu; Manurung, Rizky Briliant Syah; Endarti, Esa Wahyu; Mukti, Ria Andriani; Manurung, Muhammad Rizky Akbar (International Consortium of Education and Culture Research Studies, 2025)
Tooth extraction is a common dental procedure that carries the risk of complications such as alveolar osteitis (dry socket). Chlorhexidine digluconate, a broad-spectrum antiseptic, has been proven effective in reducing the risk of infection and accelerating wound healing following extraction. This study aims to evaluate the effectiveness of chlorhexidine usage training for dentists at National Hospital in improving competencies related to the prevention of post-extraction complications. The training was conducted as an intensive workshop comprising presentations, interactive discussions, and clinical simulations. Evaluation through pre-tests and post-tests demonstrated an average knowledge increase of 40%, while practical observations indicated enhanced skills in the correct application of the antiseptic. These results confirm that comprehensive training can improve dentists’ abilities to implement chlorhexidine use to prevent alveolar osteitis and other complications. Consequently, this program contributes to improving the quality of dental healthcare services and serves as a sustainable professional development model in clinical dental practice.